IPTEKS BAGI MASYARAKAT KELOMPOK PETERNAK LOVE BIRD DI DESA KARANGPRING KECAMATAN SUKORAMBI JEMBER - Ahmad Sauqi; Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2017)
Farm field itself is now a lot of new innovations in the development of cattle for businesses that one can mention for example Love Bird breeding birds. Departing from a hobby to maintain the bird and capture their business opportunity and market demand will determine the Love Bird breeding business is quite fast progressing. Based on the initial survey we did on Love Bird breeder in the village Karangpring Sukorambi District of Jember, we get the information that is generally berternak Love Bird was able to provide financial benefits sizable despite the problems in the breeding of course also quite complicated. Success in rake clappers means should succeed the survival rate of saplings Love Bird as a seedling that will be sold. When breeders Love Bird in the village Karangpring need their assistance, particularly related to how berternak Love Bird for the level of living seedling Love Bird higher which will need to bring an expert or breeders Love Bird already successful and experienced to provide information or knowledge that is required by the Love Bird breeders in the village Karangpring. The high rate of mortality of tillers Love Bird on farmers in the village of Karangpring also supported by the enclosure in which the minimal number of factors make the cage puppies should be collected so that the late indukannya premises separated when broodstock estrus then saplings can be killed by his own mother. In addition to concerns about the cage / cage, death tiller Love Bird also be caused by inadequate intake of nutrients from the feed are usually given to the need for knowledge transfer from practitioners breeder Love Bird who is experienced in making the feed mixture that can be done alone, and of course the cost will be relatively more cheaper than buying in the store bird feed. Keywords: Livestock, Love Bird, Feed Production Innovation.